Concise history of muslim world - Rafi Ahmad Fidai (Kitab Bhavan, 1997)
ast jil,1 =c.1-2 jil.2 =c.1 jil.3 =c.1/oen, jil.1=c.3;jil.2=c.2;jil.3=c.32why, jil. 2=c.3; jil. 3=c.3/en, jil.1=c.14/tr, jil.2=c.4; jil.3=c.4